The role of machine learning in clinical research: transforming the future of evidence generation. - Weissler, E. Hope.; Naumann, Tristan.; Andersson, Tomas.; Ranganath, Rajesh.; Elemento, Olivier.; Luo, Yuan.; Freitag, Daniel F.; Benoit, James.; Hughes, Michael C.; Khan, Faisal.; Slater, Paul.; Shameer, Khader.; Roe, Matthew.; Hutchison, Emmette.; Kollins, Scott H.; Broedl, Uli.; Meng, Zhaoling.; Wong, Jennifer L.; Curtis, Lesley.; Huang, Erich.; Ghassemi, Marzyeh. (Tufts University. Tisch Library., 2021)
Keywords: Clinical trials as topic; Machine learning, Artificial intelligence, Research design, Research ethics.; Springer Open.